Anonymity: The Politicisation of a Concept - Thorsten Thiel (Book of Anonymity. An edited collection, 2021)
This chapter traces the changing conditions of anonymity in liberal Western societies. Political, technical, economic, and social developments have undermined the broad de facto anonymity of modern societies, and I ask whether the current politicization of anonymity is likely to have any impact on the steady disappearance of opportunities for anonymous communication. I argue that anonymity is an ambivalent but critical feature of the democratic public sphere. If we want to slow down or halt this trend, or actually reverse it, it will not be enough simply to politicize “deanonymizing ” tendencies and whip up indignation. My argument proceeds in three stages. I begin with several conceptual observations on anonymity. From these, a heuristic framework emerges with which the changes in anonymous communication, and in the role this form of communication plays in society, can be described. In very broad brushstrokes, I then describe and analyze the extent to which options for anonymity have been affected by the revolution in information and communication technologies (ICTs). I conclude by considering how anonymity is framed in public discourse and what effects this has. My aim in this last section is to provide a sketch of the main lines in the debates and show that none of the different layers of the anonymity discourse have generated any cogent ideas as to how the all-encompassing trend to deanonymization outlined in the second part of the chapter might be tackled. If we are to succeed in countering this trend, we will have to adopt a more political and institutional mode of thinking.
Keywords: 300; anonymity; data security; surveillance; personhood; privacy; art-science collaboration; digital cultures